Performance of a Transuretral Endoscopic Surgery Unit - Pereyra Bonasso, Jorge; Gayol Collete, Mario; Viola Peluffo, Julio; García Guido, Luis (Cirugía del Uruguay, 1981)
surgery unit covering 215 such operations on 173 patients during the course of a 12 - month period, with good results. Correctional procedures were performed on urethra, prostate, neck of bladder and terminal ureter. There wt;,re no deaths.